Community-Based Tourism Destination Management: A Conceptual Analysis through a Literature Review - Gultom, Rut Irmawati; Marbun, April; Simatupang, Suminta; Siregar, Veronica Lidia Theresia (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
The transformation of tourism destinations in the era of the creative economy has become an important topic in contemporary tourism studies. Global tourism development is increasingly influenced by globalization, technological innovation, and changes in tourist preferences toward more meaningful travel experiences. This study aims to examine how tourism destinations transform in response to these changes through a literature review approach. Relevant academic publications from 2018–2023 were collected from major databases and analyzed using thematic content analysis. The findings indicate that tourism destination transformation is driven by three major factors: the dynamics of globalization and global tourism networks, the shift from mass tourism to experience-based tourism, and the integration of creative economy activities into tourism development. The creative economy plays a crucial role in strengthening destination competitiveness through the development of innovative tourism products, cultural branding, and enhanced visitor experiences. Furthermore, collaboration among stakeholders—including local communities, government institutions, and tourism businesses—is essential to support sustainable tourism development. The study concludes that integrating creativity, culture, and innovation into tourism strategies can enhance the attractiveness and sustainability of destinations in the global tourism market.